Complementary or competitive? Interrelationships between hotels, Airbnb and housing in Tel Aviv, Israel. Issue 22 (17th November 2022) - Ram, Yael; Tchetchik, Anat
ABSTRACT: The present study explores the interrelationships between Airbnb and both the formal accommodation industry (hotels) and the housing market. We used time-series data (28-49 months) from Tel Aviv, a city where Airbnb was not regulated during the studied period. The analysis shows that Airbnb plays a dual function for the accommodation market. While it complements the demand for hotels, it competes with residents in the housing market and increases rental prices of apartments of all sizes. These results demonstrate that the effects of Airbnb listings on housing markets need to be contextualized by a broader understanding of the housing stock and the regulatory environment. From a tourism perspective, Airbnb may be relatively complementary to the formal accommodation market, especially in responding to seasonal demands. Nevertheless, regulatory issues concerning equity in meeting governmental requirements for accommodation remain essential.